2009
DOI: 10.1111/j.1469-8137.2009.03126.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose 1‐phosphate is efficiently taken up by potato (Solanum tuberosum) tuber parenchyma cells and converted to reserve starch granules

Abstract: Summary Reserve starch is an important plant product but the actual biosynthetic process is not yet fully understood. Potato (Solanum tuberosum) tuber discs from various transgenic plants were used to analyse the conversion of external sugars or sugar derivatives to starch. By using in vitro assays, a direct glucosyl transfer from glucose 1‐phosphate to native starch granules as mediated by recombinant plastidial phosphorylase was analysed. Compared with labelled glucose, glucose 6‐phosphate or sucrose, tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 44 publications
4
73
0
Order By: Relevance
“…Following the import of Glc-1-P into the amyloplasts, the subsequent incorporation into starch is mainly mediated by the plastidial phosphorylase isozyme (Pho1; Fettke et al, 2010). By contrast, in mesophyll cells, Glc-1-P imported into the chloroplast leads to the formation of ADPglucose, which then acts as a glucosyl donor for starch synthases (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the import of Glc-1-P into the amyloplasts, the subsequent incorporation into starch is mainly mediated by the plastidial phosphorylase isozyme (Pho1; Fettke et al, 2010). By contrast, in mesophyll cells, Glc-1-P imported into the chloroplast leads to the formation of ADPglucose, which then acts as a glucosyl donor for starch synthases (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Thus, the superior efficiency of the Glc-1-P-dependent labeling of starch is not unique to heterotrophic cells (compare with Fettke et al, 2010). Light stimulates the flux from both external Glc-1-P and Glc to starch, but even in darkened protoplasts, the Glc-1-P-dependent labeling of starch is higher than that of Glc in illuminated protoplasts.…”
Section: Uptake and Utilization Of External Glc-1-p By Mesophyll Protmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have supported this idea. First, Fettke et al (2010aFettke et al ( , 2012 showed that G1P was efficiently and directly incorporated into reserve starch granules in potato tuber cells, suggesting the G1P pathway functions in parallel with the authentic AGPase pathway in starch biosynthesis. Second, Hwang et al (2010) proved that rice Pho1 could elongate MOS to be used by SS in the glucan synthetic direction even under physiological conditions of high Pi/G1P concentrations.…”
Section: Starch Biosynthesis and Its Degradationmentioning
confidence: 99%
“…They also assumed that some unknown factor(s) which can function and/or is(are) expressed only at higher temperatures above 20 ı C support(s) the role of Pho1. Fettke et al (2010Fettke et al ( , 2012 have examined a specific incorporation behavior of glucose 1-phosphate (G1P) by potato tuber discs from various transgenic lines and found that the exogenously added G1P was converted to native starch granules in tubers as mediated by Pho1 (Fettke et al 2010). The rate of incorporation of G1P was much higher than glucose, glucose 6-phosphate (G6P), or sucrose.…”
Section: Plastidial Phosphorylase (Pho1)mentioning
confidence: 98%